Emphysematous Pyelonephritis and Hiccups, a Case Report (Iranian Journal of Kidney Diseases, 2020)
The initial manifestation of emphysematous pyelonephritis (EPN) with hiccups is extremely rare. We report a 47-year-old diabetic man with complaint of persistent hiccups as the first manifestation. Class 3B EPN was confirmed based on findings of Contrast-enhanced abdominal multi-slice CT scan. There were no neurologic deficits, Medications that lead to hiccups and gastrointestinal dysfunction. Our patient was treated with antimicrobial therapy and double J stenting. His hiccups completely resolved in one week and had no relapse.